Prevalence, Risk Factors, and Clinical Outcomes of Anemia Among Adult Males and Females Attending a General Medicine Outpatient Department. A Cross-Sectional Study - Sohaib Akbar, Qurratul Ain, Rabia Rasheed, Ambreen Asif, Kashif Aziz Ahmad, Rabea Rashed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anemia is a common and underdiagnosed condition affecting individuals globally, with particularly high prevalence in developing countries. Adult males and females attending outpatient departments are often overlooked in anemia screening, despite its significant impact on health and productivity. Objective: To determine the prevalence, identify associated risk factors, and assess clinical outcomes of anemia among adult males and females attending the General Medicine Outpatient Department (OPD) at Lahore General Hospital, Lahore, Pakistan. Methods: A cross-sectional study was conducted over one year (June 2022–June 2023) including 150 adult patients (≥18 years) presenting to the General Medicine OPD. Hemoglobin levels were assessed using WHO criteria, and additional laboratory investigations were performed to classify anemia type and etiology. Demographic, dietary, clinical, and comorbidity data were collected using a structured questionnaire. Statistical analysis was performed using SPSS version 26.0. Results: The overall prevalence of anemia was 37.3%, with a significantly higher rate in females (50.0%) compared to males (23.6%) (p = 0.001). Iron deficiency was the most common cause (60.7%), followed by anemia of chronic disease (25.0%) and megaloblastic anemia (14.3%). Microcytic hypochromic morphology was predominant (60.4%). Common symptoms included fatigue (67.9%) and pallor (57.1%). Significant risk factors included female gender, low iron intake, heavy menstrual bleeding, chronic kidney disease, and low socioeconomic status. Conclusion: Anemia is highly prevalent among adult OPD patients, especially females. Nutritional deficiencies and chronic illnesses are key contributors. Routine screening and comprehensive outpatient interventions are essential to reduce anemia-related morbidity. Keywords: Anemia, Iron Deficiency, Outpatient Department, Risk Factors, Clinical Outcomes, Prevalence